The Impact of Blockchain on the Music Industry - Camila Sitonio; Alberto Nucciarelli (International Telecommunications Society (ITS), 2018)
This paper explores the impact of blockchain on the music industry with a focus on the implications technology can have for artists. By investigating the industry's supply chain, we argue that the on-demand streaming platforms (e.g. Spotify and Apple Music) have allowed consumers to easily access music products but have introduced a level of intermediation between artists and customers leading to inefficiency of the royalty payments systems. The goal of this research is to identify blockchain applications that would enable the disintermediation of the industry, allowing artists to create and capture more value from their own products. This paper discusses some applications and concepts related to blockchain, including smart contracts, record keeping, revenue management, and metadata analysis. By presenting some examples, we assess the current state of the technology's development in the music industry, how companies are introducing this new model into the market, and some limitations these models may have.
Keywords: 330